Native Welfare Losses from High Skilled Immigration - Alexander Kemnitz (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
This paper explores the effects of high skilled immigration to a host country with unionized low skilled labor and an unemployment insurance scheme. We show that such immigration can create a negative immigration surplus due to adverse effects on low skilled employment, provided that the elasticity between high and low skilled labor is high as empirical evidence suggests.
Keywords: F22; J65; J61; H53; J5; 330; Immigration; Trade Union; Unemployment; Elasticity of Substitution; Hochqualifizierte Arbeitskräfte; Einwanderung; Wohlfahrtseffekt; Ungelernte Arbeitskräfte; Gewerkschaftlicher Organisationsgrad; Substitutionselastizität; Arbeitslosigkeit; Theorie